Improved mechanical properties of poly (vinyl alcohol) films with glycerol plasticizer by uniaxial drawing. (3rd July 2018) - Tian, Huafeng; Yuan, Li; Zhou, Dan; Niu, Junyi; Cong, Hengjiang; Xiang, Aimin
Abstract : In this work, the uniaxial stretching poly (vinyl alcohol) (PVA) films with glycerol as plasticizer were prepared to explore the influence of drawing temperature and drawing ratio. The structure and property were investigated with scanning electron microscope, wide‐angle X‐ray diffraction, X‐ray diffraction, differential scanning calorimetry, mechanical tests, etc. With the increase of stretching temperature, the melting and crystallization temperatures increased. The tensile strength and Young modulus of glycerol/PVA films increased first and then decreased; when the temperature was 80°C, the tensile strength and Young modulus reached to maximum values of 197.2 and 470 MPa, respectively. In addition, with the increase of draw ratio, the orientation degree of the PVA molecular chains increased, indicating the improved regularity of molecular chains. When the PVA films were stretched to 4 times, the tensile strength and Young modulus of the films reached 162 and 143 MPa, respectively, which were 4 and 1.3 times compared with those of unoriented films. These environmentally friendly PVA films with excellent mechanical properties would find wide applications in the industry such as packaging, coating, etc.